Model to estimate the leaf area of combretum leprosum mart (2013)
Combretum leprosum Mart. -Combretaceae is a shrub used in popular medicine in Northeast Brazil as antiulcer, antihemorragica and antinociceptive. Estimating the leaf area is an important remark to be made biometric to compare the growth of plants. In this study, a model for calculating leaf area was developed for Combretum leprosum using linear measurements of leaf length (C) and maximum width (L), in order to obtain an equation by the linear dimensions of the leaf. It was collected 200 leaf blades of a population of C. leprosum native in a conservation area of Caatinga in the campus of the Federal Rural University of the Semi Arid in Natal, Rio Grande do Norte. The leaves were obtained from adults and leaf area was measured using an integrator leaf area (LI-3100, LI-COR). The analysis of variance of the regression was made in the program SAEG. The linear and geometric equations can be used to estimate leaf area of C. leprosum. From a practical standpoint, it is suggested to opt for the simple linear equation involving the C x L, using the regression equation A = 0.7103 x (C x L), which is equivalent to taking 71.03% of product of the length along the midrib and the maximum width, with a coefficient of determination of 0.952617.